Analysis of production planning in a global manufacturing company with process mining. Issue 2 (5th March 2018) - ER, Mahendrawathi; Arsad, Noval; Astuti, Hanim Maria; Kusumawardani, Renny Pradina; Utami, Rivia Atmajaningtyas
Abstract : Purpose: The purpose of this paper is to present the result of using process mining to model the production planning (PP) process of a manufacturing company that is supported by enterprise resource planning (ERP) systems. Design/methodology/approach: This paper uses event logs obtained from the case company's ERP database. The steps for this research are planning process mining implementation, extraction and construction of event log, discovering process model with Heuristic Miner and analysis. Findings: Process model obtained from process mining shows how the PP is actually conducted. It shows the loop in materials requirement planning and create plan order process. Furthermore, the occurrences of changing plan order date and production line indicate the schedule instability in the case company. Further analysis of the material management (MM) event log shows the implication of production plan changes on MM. Continuous change in the plan affects material allocation priority and may result in a mismatch between production needs and the materials available. Research limitations/implications: The study is only conducted in a single and specific case. Therefore, even though the findings provide good insight, the use of solitary case study does not imply a general result applied to other cases. Hence, there is a need to conduct similar studies on various cases so that a more generic conclusion can be drawn. Practical implications: The result provides insights into how the current company's policy of adjusting the production plan to accommodate changing demand impacts their operation. It can help the company to consider a better balance between flexibility and efficiency to improve their process. Originality/value: The paper demonstrates the use of process mining to capture the real progression of PP based on the data stored in the company's ERP database, which give an insight into how a real company conducts their PP process, the implication of schedule instability on MM and production. The novelty of this research lies in the use of process mining to attest to the schedule nervousness issue at a process level.